Assembly of MHC class I molecules analyzed in vitro. - Townsend, A; Elliott, T; Cerundolo, V; Foster, L; Barber, B; Tse, A (1990)
Recent evidence suggests that peptide ligands take part in the assembly of class I molecules in living cells. We now describe a simple system for studying class I assembly in vitro. Detergent extracts of the mutant cells RMA-S and .174, in which class I assembly does not occur spontaneously, will support assembly in vitro when specific peptides are added. Peptides stabilize a conformational change in the class I heavy chain and association with beta 2-microglobulin, at concentrations approximately 100-fold lower than required in "peptide feeding" experiments with whole cells. We show that peptides bind class I molecules during assembly and demonstrate that the conformational change induced in the heavy chain is influenced by the concentrations of both peptide and beta 2-microglobulin.